Respon Berbagai Bentuk, Ukuran dan Bahan Elektroda Pada Pengayaan Elektrolisis Tritium dalam Sampel Air - Hidayanto, Eko; Tjahaja, Poppy Intan; Arif, Idam (BERKALA FISIKA, 2009)
Experiments were carried out to investigate the effects of various forms, sizes and materials of electrodes in the electrolytic enrichment for the determination of tritium concentration in water sample. Electrodes were made in several forms: square plate, cylinder and spiral. The electrolytic enrichment was carried out by conducting electric current to the electrodes in electrolytic cell at 150C filled with water sample, until the water volume is reduced to 10% from the initial volume. The concentrated water were then mixed with scintillate solution, and then counted using Liquid Scintillation Counter (LSC). The results show that the appropriate electrodes is nickel square plate with the recovery fraction and the enrichment factor respectively are 73.73% and 7.373